The complete mitochondrial genome of sponge Pseudosuberites sp. (Demospongiae, Suberitida, Suberitidae) from Dokdo, Republic of Korea (East Sea). Issue 2 (3rd July 2019) - Yu, Cheol; Kang, Dong Won; Kim, Hana; Kim, Hyung June
Abstract: The mitogenome of Pseudosuberites sp. (Suberitida, Suberitidae) has been determined first in the genus Pseudosuberites . Assembled mitogenome was 23, 502 bp in length, including 14 protein-coding genes, 25 transfer RNA, and 2 ribosomal RNA genes. The order and structure are the same as those of other species belonging to the same family Suberitidae. Pseudosuberites sp. was clustered with Suberites domucula within the family Suberitidae. The mitogenome of Pseudosuberites sp. will be valuable for inferring phylogenetic relationships among members of suberitids.